FKN Facilitates HK-2 Cell EMT and Tubulointerstitial Lesions via the Wnt/β-Catenin Pathway in a Murine Model of Lupus Nephritis - Fu, Dongdong; Senouthai, Soulixay; Wang, Junjie; You, Yanwu (Frontiers in Immunology, 2019)
Fractalkine (FKN), also known as chemokine (C-X3-C motif) ligand 1, constitutes an intriguing chemokine with a documented role in the development of numerous inflammatory diseases including autoimmune disease. Specifically, it has been reported that FKN is involved in the disease progression of lupus nephritis (LN). The epithelial-mesenchymal transition (EMT) plays a significant role in the formation of tubulointerstitial lesions (TIL), which are increasingly recognized as a hallmark of tissue fibrogenesis after injury. However, the correlation between FKN and EMT or TIL in LN has not been determined. To investigate the potential role of FKN in EMT and TIL, MRL lymphoproliferation (MRL/lpr) strain mice were treated with an anti-FKN antibody, recombinant-FKN chemokine domain, or isotype antibody. Our results revealed that treatment with the anti-FKN antibody improved EMT, TIL, and renal function in MRL/lpr mice, along with inhibiting activation of the Wnt/-catenin signaling pathway. In contrast, administration of the recombinant-FKN chemokine domain had the opposite effect. Furthermore, to further explore the roles of FKN in EMT, we assessed the levels of EMT markers in FKN-depleted or overexpressing human proximal tubule epithelial HK-2 cells. Our results provide the first evidence that the E-cadherin level was upregulated, whereas -SMA and vimentin expression was downregulated in FKN-depleted HK-2 cells. In contrast, overexpression of FKN in HK-2 cells enhanced EMT. In addition, inhibition of the Wnt/-catenin pathway by XAV939 negated the effect of FKN overexpression, whereas activation of the Wnt/-catenin pathway by Ang II impaired the effect of the FKN knockout on EMT in HK-2 cells. Together, our data indicate that FKN plays essential roles in the EMT progression and development of TIL in MRL/lpr mice, most likely through activation of the Wnt/-catenin signaling pathway.